Balega Dalam Rami - Farras Annafi; Wimbrayardi Wimbrayardi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This artwork aims to interpret the phenomenon and behavior of the community at the baralek event starting from the preparation stage to the party stage equipped with the art of saluang bagurau into a new musical composition. The process of creating this artwork is carried out with the observation (exploration), experimentation (improvisation), and forming stages. The idea of the musical work "Balega Dalam Rami" was raised from the procession of preparation for the baralek event (wedding party) in Minangkabau. Baralek as a creative idea had an impact on the emergence of the composer's imagination which was then poured into the concept of garap which became a foothold to accommodate the three parts of the procession in this work, namely Bagotong Royong, Bainai Night and Bagurau, which provided an overview of how the phenomenon and behavior and emotions of the community during the preparation process for Baralek (wedding party), to an entertainment night that focused on the phenomenon that occurred in Saluang Bagurau.